A Review and Evaluation of Prediction Models of Gas Permeation for a Blended Flexible Packaging Film. Issue 4 (15th March 2016) - Ge, Changfeng; Popham, Jake
Abstract : Barrier properties of blended film, such as oxygen permeability, are a collective behaviour contributed by different resins. This study reviews 10 most widely used prediction models of gas permeation for two‐phase blended film along with their assumptions and the interconnection and similarities between these models. Two blended blown films, LDPE/EVOH and PET/PEN, were produced representing two different permeability ratios of matrix‐to‐disperse phase. Effective oxygen permeability of the blended films was predicted by the models and compared with measured values. Scanning electron microscopy (SEM) micrographs of both films were obtained to understand the morphology in relation to gas permeation. The Fricke model and the effective medium theory model are recommended in this study to predict effective permeability of a blended flexible packaging film. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study reviewed ten of the most used prediction models of gas permeation for a two‐phase blended film. Low density polyethylene/ethylene vinyl alcohol copolymer and polyethylene terephthalate/polyethylene naphthalate blown films were produced, representing two different permeability ratios of matrix to disperse phase. The measured and model predicted oxygen permeability of the two films was compared. The Fricke model and the effective medium theory model are recommended in this study to predict the effective permeability of a blended flexible packaging film.